2020
DOI: 10.1016/j.ekir.2020.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Etiologies, Clinical Features, and Outcome of Oxalate Nephropathy

Abstract: Background: Oxalate nephropathy is a potentially underestimated cause of kidney failure characterized by massive deposition of calcium oxalate crystals in the renal parenchyma. The prevalence and modes of presentation of this entity are ill-defined. Methods: Here we report on the largest consecutive series of cases of adult oxalate nephropathy diagnosed on native kidney biopsies from January 2010 to December 2018 in the UCLouvain Kidney Disease Network. Results: We screened 2265 native kidney biopsies and iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
60
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(68 citation statements)
references
References 26 publications
(71 reference statements)
3
60
1
Order By: Relevance
“…In addition, it was hypothesized that different forms of oxalate deposition may influence disease manifestation: severe acute supersaturation may cause massive crystal deposition, renal epithelial cell damage, inflammation and necrosis, resulting in AKI. On the contrary, less severe but persistent forms may generate chronic crystal deposition, especially in the distal tubule or collecting ducts, ending in CKD [108,109]. Although prospective studies are lacking, a large number of case reports suggested a causative role of dietary oxalate on acute kidney injury.…”
Section: Acute Kidney Injurymentioning
confidence: 99%
“…In addition, it was hypothesized that different forms of oxalate deposition may influence disease manifestation: severe acute supersaturation may cause massive crystal deposition, renal epithelial cell damage, inflammation and necrosis, resulting in AKI. On the contrary, less severe but persistent forms may generate chronic crystal deposition, especially in the distal tubule or collecting ducts, ending in CKD [108,109]. Although prospective studies are lacking, a large number of case reports suggested a causative role of dietary oxalate on acute kidney injury.…”
Section: Acute Kidney Injurymentioning
confidence: 99%
“…This study describes characteristics of AKD with secondary renal oxalosis case series, which is clinically more common than PH, but a potentially underestimated disease. Oxalate crystals deposition in the kidney causes tubule obstruction and interstitial inflammation, leading to renal dysfunction [ 12 , 13 ]. As early as 1973, William R. Salyer and colleagues described oxalosis as a severe complication of chronic renal failure [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recently published study reported oxalate nephropathy had a prevalence of 1% as the cause of native kidney disease. Disease origins from chronic pancreatitis and gastric bypass were the most common (48%) [ 13 ]. However, analysis of AKD with renal oxalosis in the present study showed a different etiological composition from that reported by Western researchers, where only 26.1% of patients having risk factors by enterogenous or excessive oxalate intake, but new AKD was regarded as the cause of oxalosis in these patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Ultrasound of the kidneys is usually unyielding in oxalate nephropathy as seen in observational studies. 3,4 Severe acute kidney failure was not uncommon and transient renal replacement therapy was required in 60-70%, 2 but prognosis was generally good with renal recovery within 2-8 weeks. 1 Oxalate nephropathy is uncommon and may be due to primary or secondary hyperoxaluria.…”
mentioning
confidence: 99%